Practice of using the Internet in fighting crime against monuments - Grajewski, Adam (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
We are seeing a change in the development of science, which draws forensics knowledge and use of the achievements, adapting them to fight crime. Modern forensics does not stop at the same adaptation of the achievements of other sciences, but also independently develops its own methods and means of fighting crime, which is associated with ongoing technological progres and the growing needs of law enforcement and forensics. Collected during the activity traces of forensic science today, we can identify using modern technologies. It is now possible, thanks also obtained new sources of personal and work hard analytical, investigative and operational. As practice shows the basis for the initiation of proceedings may also be electronic evidence, which can be found by analyzing the content of the Internet.